Welcome :: Homework Help and Answers :: Mathskey.com
Welcome to Mathskey.com Question & Answers Community. Ask any math/science homework question and receive answers from other members of the community.

13,435 questions

17,804 answers

1,438 comments

120,996 users

Solve for the variable?

0 votes

log(-3x -1) = log(-4x-6)

asked Mar 28, 2013 in ALGEBRA 2 by andrew Scholar

1 Answer

0 votes

log(- 3x - 1) = log(-4x - 6)

Take out logarithm to each side

-3x - 1 = - 4x - 6

Multiply each side by negative one

3x + 1 = 4x + 6

Subtract 3x from  each side

3x -3x + 1 = 4x - 3x + 6

0 + 1 = x + 6

Recall : Symmetric  property a = b then b = a and additive identity 0, 0 + a = a + 0 = a

x + 6 = 1

Subtract 6 from each side

x + 6 - 6 = 1 - 6

x + 0 = -5

There fore x = -5.

answered Mar 28, 2013 by diane Scholar

Related questions

asked Jul 25, 2014 in ALGEBRA 2 by anonymous
asked Dec 24, 2017 in PRECALCULUS by anonymous
asked Nov 13, 2014 in ALGEBRA 2 by anonymous
asked Dec 22, 2017 in PRECALCULUS by anonymous
...